Clinical Utility of Prothrombin Fragment 1+2, Thrombin Antithrombin III Complexes and D-dimer Measurements in the Diagnosis of Deep Vein Thrombosis following Total Hip Replacement - Cofrancesco, E.; Cortellaro, M.; Corradi, A.; Ravasi, F.; Bertocchi, F. (Thrombosis and Haemostasis, 1998)
Background: Measurements of prothrombin fragment 1+2 (F1+2), thrombin antithrombin III complexes (TAT) and D-dimer plasma levels have been proposed as non-invasive screening tests to exclude postoperative deep venous thrombosis (DVT). We investigated the diagnostic efficacy of these coagulation activation markers to rule out postoperative DVT in patients undergoing hip surgery under antithrombotic prophylaxis. Methods: In this substudy of a randomized double-blind thrombosis prophylaxis trial comparing three doses of desirudin (10, 15 or 20 mg b.i.d.) with unfractionated heparin (5000 IU t.i.d.) we used ELISA procedures to measure F1+2, TAT and D-dimer in 159 patients undergoing total hip replacement at baseline (day 0) and on postoperative days 1, 3 and 6. Bilateral venography was performed in all cases 8-11 days after surgery. Results: For the F1+2 assay sensitivity ranged from 73 to 83% in the three postoperative days investigated, and negative predictive value (NPV) from 68 to 74%. For TAT and D-dimer sensitivity ranged from 71 to 73% and from 71 to 83% and NPV from 61 to 65% and from 61 to 74% respectively. Interpretation: In terms of sensitivity and NPV F1+2 and D-dimer are equivalent and are superior to TAT. However, their accuracy is too low to rule out the presence of DVT after hip surgery under antithrombotic prophylaxis.